2019
DOI: 10.3390/medicina55100659
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Program Combined with Local Vibroacoustics Improves Psychophysiological Conditions in Patients with ACL Reconstruction

Abstract: Background and objective: This study investigated the therapeutic effect of applying local body vibration (LBV) with built-in vibroacoustic sound on patients who had an anterior cruciate ligament (ACL) reconstruction. Materials and Methods: Twenty-four participants were randomly classified into a LBV group (LBVG; n = 11) or a non-LBV group (nLBVG; n = 13). Both groups received the same program; however, the LBVG received LBV. Psychological measures included pain, anxiety, and symptoms; physiological measures i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
(42 reference statements)
0
7
0
1
Order By: Relevance
“…Twelve studies were eliminated because they did not report essential quantitative data, e.g., mean and its corresponding standard deviation (SD), or were congress abstracts or online abstracts studies for which we could not get the full text despite contacting their corresponding author for more information via email. Finally, we assessed 13 studies in the quality assessment stage to import for analysis [23][24][25][26][27][28][29][30][31][32][33][34][35] (Fig. 1).…”
Section: Study Selection Quality Assessment and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies were eliminated because they did not report essential quantitative data, e.g., mean and its corresponding standard deviation (SD), or were congress abstracts or online abstracts studies for which we could not get the full text despite contacting their corresponding author for more information via email. Finally, we assessed 13 studies in the quality assessment stage to import for analysis [23][24][25][26][27][28][29][30][31][32][33][34][35] (Fig. 1).…”
Section: Study Selection Quality Assessment and Characteristicsmentioning
confidence: 99%
“…Table 2 presents details of the risk of bias assessment of the included studies. To summarize, the risk of bias was low in six studies [23,24,[32][33][34][35], high in five studies [25,[28][29][30][31], and unclear in one study [26].…”
Section: Study Selection Quality Assessment and Characteristicsmentioning
confidence: 99%
“…Coulondre et al showed that LBV improved knee extension muscle strength ( p < 0.05) but did not improve knee function ( p > 0.05). Similarly, Ming et al reported that LVT improved quadriceps muscle strength and knee ROM [ 44 ]. Other studies should be evaluated with caution, as they are individual studies investigating individual interventions, so they should not lead to far-reaching conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…HRV data were collected at baseline (M0), 3 months (M3), 6 months (M6), and 9 months (M9) by uBioMacpa (Certificate by KFDA; BioSensecreative Co. Ltd., Seoul, Korea) and its embedded software [ 32 , 33 ]. Before the HRV test, participants were asked to refrain from smoking or consuming alcohol, coffee, and energy drinks for at least 8 h but were allowed to drink some water.…”
Section: Methodsmentioning
confidence: 99%